Sustainable cultural heritage landscape: an imaginary journey inside the veins of deserts - Mousazadeh, Hossein; Zhu, Kai; Ghorbani, Amir; Akbarzadeh Almani, Farahnaz; Arabi, Maral; Parvar, Fatemeh; Dávid, Lóránt Dénes (Frontiers in Sustainable Food Systems, 2023)
Introduction Travel narratives are very attractive sources that examine the destination from the point of view of tourists with different attitudes. A group of studies has been conducted on travel narratives, but this type of analysis has been done very little in Iran despite their potential. Methods 11 Persian qanats (PQs) have been recognized as UNESCO World Heritage sites. Visitors who explore the qanats as conduits of the desert have extraordinary experiences that can seem like captivating fiction. The main focus of the current research is on the narratives of tourists who have visited these PQs. Qualitative and narrative analysis methods were used to avoid relying on numerical data. Results The study includes 30 participants who had visited the qanats and shared their travel stories. The study findings show that Persian qanats are a distinctive draw for foreign tourists that can leave a lasting impression. Discussion The PQs listed as a UNESCO World Heritage property are one of the unique attractions of Iran’s tourism, so far its tourism potential has been less noticed, and qanat tourism is a nascent branch of tourism in Iran. The narratives of travelers can be instrumental in promoting this invaluable groundwater engineering heritage.